2022
DOI: 10.1029/2021jb023532
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthally Anisotropic Structure in the Crust and Uppermost Mantle in Central East China and Its Significance to Regional Deformation Around the Tan‐Lu Fault Zone

Abstract: Seismic anisotropy can be linked to different mechanisms, structures, and sources. We constrained the 3‐D depth‐dependent shear wave speed isotropic and azimuthally anisotropic structures with Rayleigh wave phase velocity from ambient noise in central Eastern China. We compared the results with other models and found that in the upper crust, the maximum horizontal stress direction differs mainly from the anisotropy that coincides with the strikes of major faults and geologic structures. We inferred that the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
(217 reference statements)
1
3
0
Order By: Relevance
“…They are almost perpendicular to the fast direction of the crustal anisotropy within the TLFZ and NCB. This is consistent with recent surface wave studies of the southern part of the TLFZ, where the crust and upper mantle also have different deformation patterns (Bem et al., 2022; Luo & Yao, 2021). In addition, such a discrepancy was also seen in western US, where SKS data show a near E‐W fast direction largely attributed to asthenospheric flow (Silver & Holt, 2002), while P ms data near the San Andreas Fault exhibit a fault parallel NW‐SE direction (Audet, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They are almost perpendicular to the fast direction of the crustal anisotropy within the TLFZ and NCB. This is consistent with recent surface wave studies of the southern part of the TLFZ, where the crust and upper mantle also have different deformation patterns (Bem et al., 2022; Luo & Yao, 2021). In addition, such a discrepancy was also seen in western US, where SKS data show a near E‐W fast direction largely attributed to asthenospheric flow (Silver & Holt, 2002), while P ms data near the San Andreas Fault exhibit a fault parallel NW‐SE direction (Audet, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Recent surface wave studies (Bem et al., 2022; Luo & Yao, 2021) indicated that azimuthal anisotropy in the crust beneath the southern segments of the Tanlu fault has a fast propagation direction parallel to the fault, suggesting a different deformation pattern between the crust and underneath mantle lithosphere around the fault. In theory, it is difficult to measure azimuthal anisotropy using surface waves propagating in different directions because of the tradeoff between anisotropy and heterogeneities along raypaths.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a rotation of the fast axis direction from roughly WNW-ENE to NW-SE proximal to the Japan sea coast may be indicating the existence of different deformation patterns resulting from stress changes towards the coast. Several studies have demonstrated that anisotropy observed in the upper crustal structure is associated primarily with the structural fabric and stress-induced microcracks alignment, with the fast axes directions aligning with these microcracks (Bem et al 2022;Crampin 1978;Crampin and Peacock 2008;Yang et al 2018).…”
Section: Northwestern Part Of the Kinki Regionmentioning
confidence: 99%
“…manuscript submitted to Earth, Planets and Space Geological heterogeneities can be well constrained by isotropic seismic velocities obtained from high-resolution seismic tomographic inversions (e.g., Nakajima and Hasegawa 2007;Nishida et al 2008;Nthaba et al 2022;Matsubara et al 2008). However, the geodynamic processes that cause deformation and generate destructive earthquakes can be revealed by a seismically observable phenomena referred to as anisotropy (Chen et al 2018;Hiramatsu et al 2010;Teanby et al 2004), which reflects the directional variation of seismic velocity (Bem et al 2022).…”
Section: Introductionmentioning
confidence: 99%